An e-Monitoring System for Patients with Non-Communicable Diseases: A Case of Beni County in the Democratic Republic of Congo - Josiane Heri; Allan Omondi (IJAIT (International Journal of Applied Information Technology), 2022)
Non-Communicable Diseases (NCDs) are the leading causes of morbidity and mortality globally. 80% of these deaths occur in low- and middle-income countries whose fragile health systems are still grappling with a heavy burden of infectious diseases resulting in a duo burden of disease. While early detection increases the survival rate and ensures a favorable prognosis for most NCDs, about 80% of reported cases are detected at an advanced stage when little can be achieved in treatment. A few such patients are directed to palliative care in hospices. Some challenges include low awareness of NCDs' signs and symptoms, poor treatment, and inadequate early detection and monitoring services. Data collection was done through observation, personal experience, and interviews in the Beni, Democratic Republic of Congo population. The collected data was analyzed to identify the system requirements for a computer-based information system that supports the management of NCDs in rural areas. The findings propose an analytical application software that applies correlation and regression analysis techniques to analyze patients' vitals. This is to be used by community health workers/volunteers, administrators in health care facilities, and medical doctors to support the implementation of early interventions to prevent NCDs from getting worse at an avoidable rate. The system was developed based on an Object-Oriented Analysis and Design (OOAD) approach using the V-Shaped system development methodology. Functional testing was conducted to test the system, and the result for each functionality was successful.